Johannesburg, sex love and money: an ethnography of phones and feelings - Masango, Lebohang (My University, 2019)
Compensated relationships between younger women and older, moneyed men have been established as the cause of new HIV infections in South African women aged 15 – 24 years old. A great portion of the literature on young love in South Africa reproduces the connection between compensated relationships and illness. In this dissertation, I establish how young women in Johannesburg define and practice love and intimacy in their compensated relationships in the era of social media and the #blessed lifestyle. It highlights the spaces and relationships that inform their romantic choices. The research setting is Johannesburg and social media. The methods that are used this study are face-to-face and WhatsApp interviews as well as participant observation on Twitter. I argue that social media use is reconfiguring the meanings of love and intimacy for young women in Johannesburg. The physical context affects their views and actions around their relationships. Through increasing engagements in virtual spaces, young women recognise their individual choices to date with compensation as a response to the wider social vulnerability collectively experienced by women in private and public spaces all over South Africa. In response to that danger, young women use their individual romantic relationships to supplement their lifestyles monetarily in the case of personal endangerment as well as for pleasure.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Social Anthropology March 2019
Keywords: Students--Sexual behavior--South Africa; Youth--Sexual behavior--South Africa